1990
DOI: 10.3102/00346543060004517
|View full text |Cite
|
Sign up to set email alerts
|

When Children and Adults Do Not Use Learning Strategies: Toward a Theory of Settings

Abstract: Strategies enhance learning. However, children and adults often fail to invoke strategic behaviors. In this article, five reasons for failure to use strategies are discussed: (a) poor cognitive monitoring, (b) primitive routines that yield a product, (c) a meager knowledge base, (d) attributions and classroom goals that do not support strategy use, and (e) minimal transfer. I argue that use and failure to use strategies are not fruitfully studied without consideration of setting. A theory of settings reminds u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0
8

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(165 citation statements)
references
References 40 publications
7
150
0
8
Order By: Relevance
“…Many researchers exploring strategic processing (e.g., Baumann, 1984;Pressley, Goodchild, Fleet, Zajchowski, & Evans, 1989), ourselves included (e.g., Garner & Alexander, 1989), have focused on the cognitive, metacognitive, and affective attributes of learners, and have attended only tangentially to contextual factors as relevant to strategic behavior (cf. Garner, 1990). Yet, this study suggests that the actions of the teacher must be carefully considered, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers exploring strategic processing (e.g., Baumann, 1984;Pressley, Goodchild, Fleet, Zajchowski, & Evans, 1989), ourselves included (e.g., Garner & Alexander, 1989), have focused on the cognitive, metacognitive, and affective attributes of learners, and have attended only tangentially to contextual factors as relevant to strategic behavior (cf. Garner, 1990). Yet, this study suggests that the actions of the teacher must be carefully considered, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that students may not continue to use useful strategies outside of the context in which they are taught (Garner, 1990;Derry & Murphy, 1986). In common with their younger peers, adult learners tend to focus their study efforts towards passing the test, and not on the acquisition of the knowledge and skills they will need to proceed to the next level of their education.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the task-based hypothesis tacitly adopts the view that comprehension and strategy use are based on the reader's particular goals for reading. One instructional implication of this view is that readers should be encouraged to construct meaningful goals prior to reading and use these goals to guide their comprehension (Garner, 1990).…”
Section: (I993)-mentioning
confidence: 99%